Odpowiedź :
Odpowiedź:
2.
2x + (5x - 6) = 2x + 5x - 6 = 7x - 6
3.
4a - (7a + 8b - c) = 4a - 7a - 8b + c = - 3a - 8b + c
4.
4g - (- 5h - 3g + k) = 4g + 5h + 3g - k = 7g + 5h - k
5.
2(ab + c) = 2ab + 2c
6.
- 8(2x - 4k = - 16x + 32k
7.
(3xy - 2x²)( - 5) = - 15xy + 10x²
8.
(18p - 6k + 2) : 3 = 18p/3 - 6k/3 + 2/3 = 6p - 2k + 2/3
9.
(4g -6)/( - 2) = - 4g/(- 2) - 6/(- 2) = 2g + 3
10.
- 5ab + 3(2ab - 3) - (2a - 3b) = - 5ab + 6ab - 9 - 2a + 3b = - 2a + ab + 3b - 9
11.
- (x + y) - 2( - x - y) = - x - y + 2x + 2y = x + y
12.
(12g - 4)/4 + (10g + 1)/5 = [5(12g - 4) + 4(10g + 1)]/20 =
= (60g - 20 + 40g + 4)/20 = (100g - 16)/20 = 4(25g - 4)/20 =
= (25g - 4)/5
/ - znaczy kreska ułamkowa
13
- (12k - 5) + (64k - 8) : (- 8) + 6 = - 12k + 5 + 64k/(- 8) - 8/(- 8) + 6 =
= - 12k + 5 - 8k + 1 + 6 = - 20k + 12